Konsep dan Aplikasi Layanan Dukungan Sistem sebagai Komponen Program Konseling Komprehensif: A Literature Review - Yondris Yondris; Ardimen Ardimen; Dasril Dasril (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
The aim of this study is to explore the concept and application of system support services as a component of a comprehensive counseling program. This research method uses literature review by collecting and analyzing journal texts and reference books, both those found from printed sources and electronic sources in the form of ebooks and ejournals that are accessed online. The data analysis technique used is content analysis and the data is classified based on research issues and problems. The results of the study show that system support services are management activities, network development, collaboration between BK teachers/counselors and various parties including collaboration with subject teachers, administrative staff, parents, other relevant experts and continuous professional development strengthened by policy. head of the education unit to achieve the goals of guidance and counseling services. The purpose of the system support service is to facilitate the development of students with various comprehensive strategies from all school personnel without relying solely on the skills of BK teachers/counselors through counseling services. Although system support services are indirect services to students, these services have an impact on three other direct services, namely; basic services, responsive services, and individual planning services. Guidance and counseling service programs in schools are not only determined by the expertise and skills of BK teachers, but are also largely determined by the commitment and skills of all school personnel, especially the skills of principals, subject teachers, administrative staff, and other personnel.